Evaluating the survival outcomes in clinical node stage 2 and 3 breast cancer patients with negative sentinel lymph node biopsy after neoadjuvant chemotherapy: sentinel lymph node biopsy alone vs. axillary lymph node dissection - Shin, Eunju; Yoo, Tae-Kyung; Kim, Jisun; Chung, Il Yong; Ko, Beom Seok; Kim, Hee Jeong; Lee, Jong Won; Son, Byung Ho; Lee, Sae Byul (Frontiers in Oncology, 2025)
PurposeWith the advancement of neoadjuvant chemotherapy (NAC), the reliance on surgical removal of axillary for high-risk breast cancer is diminishing. However, there is a lack of data on the oncologic safety of sentinel lymph node biopsy (SNB) alone in patients with clinical node stages 2 and 3 who show a favorable response to NAC. This study aims to compare the oncologic outcomes of SNB alone versus SNB combined with axillary lymph node dissection (ALND) in this patient cohort.MethodsConducted at Asan Medical Center, this retrospective study analyzed data from breast cancer patients treated with NAC between 2008 and 2021. Propensity score matching (PSM) was employed to compare patients based on treatment approach. SNB was performed on patients demonstrating significant response to NAC with minimal nodal involvement and ALND was reserved for cases with negative SNB results, as determined by the operating surgeon. The study evaluated oncologic safety by comparing axillary recurrence-free survival (ARFS), regional recurrence-free survival (RRFS), and overall survival (OS) across surgical methods.ResultsOver a median follow-up of 44 months, the overall axillary recurrence rate was 2.3%, and the univariate and multivariate analyses showed no statistically significant differences in ARFS, RRFS, and OS between the groups. Propensity score-matched analysis further confirmed the absence of significant differences in 5-year ARFS, RRFS, and OS outcomes between the SNB-only and ALND groups.ConclusionsThis study demonstrates that performing sentinel node biopsy alone is feasible in patients with clinical node stage 2–3 after neoadjuvant chemotherapy. The findings suggest the potential for de-escalation of axillary management in these patients, which could be further explored in follow-up studies.